Optimal Design of 35T Drive Axle Housing Assembly based on Abaqus - Yanping Liu; Fangjun Lin; Hailong Wang; Kai Zhang; Zhifeng Liu (Jixie chuandong)
The 35T drive axle is a large-tonnage truck axle. In the process of use，there are some faults，such as shaft head ring seam welding crack，body square to round transition section fracture and body reinforcement crack，which are confirmed by Abaqus finite element analysis to be caused by insufficient strength of axle housing. Through the finite element analysis of rigidity and strength，Fe-safe fatigue life analysis under three road conditions，the analysis of two optimization schemes of machining and cost comparison，the structure of the axle housing is improved. The reliability of finite element analysis process is verified by bench test of axle housing assembly vertical bending stiffness. Through finite element analysis，bench test and market feedback，it is proved that the structure improvement is effective，which has certain guiding and reference significance for similar products.